HUBUNGAN ANTARA DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JANGKIT PADA SISWA PUTRA KELAS XI SMAN 1 KAMPAR TIMUR - Tengku Zulharfaini; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine whether there is a correlation the between leg muscles explosive power and triple jump results at men’s student in class XI SMAN 1 kampar timur. The forms of this research are the correlation study it look at the correlation beween leg muscle explosive power and triple jump results at men’s student in class XI off SMAN 1 Kampar Timur. As for the independent variable is the leg muscle explosive power that is symbolized by (X) and the dependent variable is the result triple jump that is symbolized (Y) at men’s student in class XI kampar timur. the population in this study from the men's student in class SMAN 1 Kampar timur. In this study researchers took sample of 25 % the total population that is 30 people. The from analysis of data obtained by the correlation coefficent of = 0,688> of = 0,367. Meaning there is a correlation the between leg muscle explosive power and triple jump results. Where the provisions of the correlation of variabel with another variabel that is determined from the > .Keywords: explosive power and triple jump